Pulmonary artery sarcoma masquerading as pulmonary embolism: the pivotal role of sonographic differentiation — a case report - Wang, Yahong; Zhao, Peng; Li, Wanyan; Wang, Lihong (Frontiers in Oncology, 2026)
Pulmonary artery sarcoma (PAS) is a rare and highly aggressive malignancy. It often presents with nonspecific clinical symptoms and is frequently misdiagnosed as pulmonary embolism (PE). Studies suggest that approximately 50% of PAS cases are initially misdiagnosed as PE. The discovery in this case report was an incidental finding. We describe the case of a patient admitted with chest tightness and chest pain. Due to a history of coronary stent implantation for 10 years, acute coronary syndrome was initially considered. Echocardiography was carried out primarily to assess cardiac condition. However, the examination revealed a hypoechoic mass in the main pulmonary artery with morphological features atypical for PE. Computed tomography angiography (CTA) was therefore recommended for further evaluation. Although the initial CTA interpretation suggested PE, the discordance between the echocardiographic and CT findings prompted the immediate initiation of anticoagulation therapy alongside a concurrent multidisciplinary consultation. The consensus following the discussion indicated a high probability of PAS. The patient subsequently underwent surgery at another hospital, and the postoperative pathology confirmed PAS. To our knowledge, current reports on PAS focus predominantly on findings from CTA, MRI, and PET-CT, while echocardiographic features are often only mentioned cursorily. However, echocardiography offers a unique capability for dynamic assessment of the tumor, which is not available with other imaging modalities. The aim of this report is to enhance the understanding of the echocardiographic manifestations of PAS, thereby facilitating earlier detection and potentially creating opportunities for surgical intervention.